Policy provisions for agricultural development in Nepal: A review. (10th July 2020) - Khanal, Narendra Raj; Nepal, Pashupati; Zhang, Yili; Nepal, Govind; Paudel, Basanta; Liu, Linshan; Rai, Raju
Abstract: In this study, the policy provisions, including legislative and institutional arrangements, made for agricultural development in Nepal are evaluated. The gaps and constraints are identified and mechanisms to reduce the gaps and address constraints are proposed. This study is primarily based on the review of literatures accompanied with the Key Informant Interviews (KIIs). Information on the key achievements and the challenges for achieving the goals of Agriculture Development Strategy (ADS) were obtained through KIIs. Altogether 10 key informants consisting of policy makers, government administrators and experts were selected. Despite government efforts to develop agriculture since the 1960s, the growth rate has remained very low. Some of the gaps and constraints limiting agricultural growth include: inappropriate approaches in designing agricultural policies, plans, and programs; inadequate and in some cases contradictory legislative provisions; low institutional capacity; and weak coordination between key stakeholders in formulating and implementing the sectoral policies. Also limited monitoring, evaluation, and analysis of activities and timely revision of the policies, programs, and acts using feedback have limited the outcome in terms of agricultural growth. Agriculture Development Strategy (ADS), 2015–2035, is hoped to be a milestone in transforming the agriculture sector from subsistence to commercialization. However, pragmatic implementation of the ADS is a major challenge. Strong political commitment and the active and positive involvement of stakeholders are needed to redesign programs and activities as per the restructuring the governance systems – federal, provincial and local levels. ADS should be mainstreamed into national and sectoral development frameworks, which would ensure effective coordination between agencies at different levels of governance. Highlights: Despite government policy provisions for accelerated growth rate, it remained slow. Holistic approach with adequate legal and institutional provisions are necessary. Policy should avoid contradictory and overlapping provisions with strong coordination. Timely revision in policy with feedbacks from monitoring and evaluation is necessary. Political stability and commitments are necessary for achieving accelerated growth.